Central type primitive neuroectodermal tumor/neuroblastoma of the uterus: A case report. Issue 10 (11th August 2014) - Shimada, Chisa; Todo, Yukiharu; Okamoto, Kazuhira; Akashi, Daisuke; Yamashiro, Katsushige; Hasegawa, Tadashi
Abstract We encountered a 63‐year‐old woman who had a uterine tumor with peritoneal dissemination and para‐aortic lymph node metastasis. Microscopic specimens of the tumor showed a small blue round‐cell tumor. Immunohistochemistry showed cells to be negative for cytokeratin AE1/3, desmin, myogenin, CD10, CD34, and CD99, focal positive for vimentin, and positive for muscle‐specific actin (HHF‐35), neurofilament, synaptophysin and CD56. Fluorescence in situ hybridization revealed no split signal showing Ewing sarcoma breakpoint region 1 gene translocation. Deletion of 1p36 was identified in 30% of the tumor cells. These findings are thought to be equivalent to central type primitive neuroectodermal tumors/neuroblastoma. Cytoreductive debulking surgery followed by chemotherapy, including cyclophosphamide, vincristine and adriamycin, resulted in complete remission. She has no evidence of disease at 24 months after surgery.